A look at 5G and future mobile communication development trend from the point of WRC-19 agenda items - Jian FANG; Ying ZHU; Na ZHENG; Pengpeng LI (Dianxin kexue)
Firstly，global 5G development status was outlined.And the relationship between world radio communication conference（WRC）and mobile communication development was introduced.Based on the application scenarios in the ITU-R recommendation of 5G visions，two important 5G scenarios，mobile internet and internet of things were analyzed.Then those WRC-19 agenda items which related to 5G were sorted out combined with the results of WRC-15.The background and core tasks were illustrated.Finally，the global technology and spectrum status of research were summarized and the future study tendency was pointed out.